Construction and Characterization of Organic Solar Cell and Study the Operational Properties - Majeed, Majid H.; Kareem, Mohamed Abdul; Ali, Esraa H. (Al-Khwarizmi Engineering Journal, 2018)
This article reviews the construction of organic solar cell (OSC) and characterized their optical and electrical properties, where indium tin oxide (ITO) used as a transparent electrode, “Poly (3-hexylthiophene- 2,5-diyl) P3HT / Poly (9,9-dioctylfluorene-alt-benzothiadiazole) F8BT” as an active layer and “Poly(3,4-ethylenedioxythiophene)-poly (styrene sulfonate)” PEDOT: PSS which is referred to the hole transport layer. Spin coating technique was used to prepared polymers thin film layers under ambient atmosphere to make OSC. The prepared samples were characterized after annealing process at (80 ͦ C) for (30 min) under non-isolated circumference. The results show a value of filling factor (FF) of (2.888), (0.233) and (0.28) and power conversion efficiency (PCE) of (0.0055), (3.333 10-6) and (0.0004), where these results were obtained by Keithley Electrometer Model 6517B, while spectral response is being utilized by LEOI-94 Monochromator and Keithley 6517B Electrometer.